Price Strategy, Market Orientation, and Business Performance in the Hotel Industry - Sampaio, Carlos (2021)
This study seeks to study the relationship between market orientation and business performance and to evaluate the mediating effect of adopting a low-price strategy in this relationship in the hotel industry. A sample from the Spanish and Portuguese hotel industry is used. Results show that the effect of market orientation on business performance is positive and direct. On the other hand, the results do not confirm the mediating effect of a strategy based on low-price in the strength of this relationship. Moreover, results indicate that a price strategy based on low-price is negatively related to hotel business performance.